Malignant Transformation in Vestibular Schwannoma: Clinical Study With Survival Analysis - Li, Jiuhong; Wang, Qiguang; Zhang, Menglan; Zhang, Guisheng; Zhang, Si; Hui, Xuhui (Frontiers in Oncology, 2021)
Aim Vestibular schwannomas (VSs) are generally considered benign tumors, and malignant transformation of VSs (MTVSs) are rare findings. The clinical features, treatment strategy, outcomes and prognostic factors remain unclear. We endeavored to analyze the natural history, management, outcomes and prognostic factors of MTVSs. Materials and Methods The clinical features, radiologic findings, pathological investigations and surgical outcomes of 4 patients with MTVSs treated at the authors’ institution between 2010 and 2019 were retrospectively collected. Related literature published until December 2019 (63 articles, 67 patients) was evaluated. The authors also made a pooled analysis to evaluate the risk factors for overall survival (OS) time. Results Of the 4 cases in our series, 3 cases were malignant transformation following previous treatment (surgery and radiosurgery) and 1 was primary MTVS. Of the 71 MTVSs from the literature, 27 were male and 39 were female, with the mean age of 47.2 ± 17.5 years old. Twelve patients (18.5%) were diagnosed with NF2 (15.4%) or NF1 (3.1%). Forty-three (61.4%) patients underwent previous treatment (surgery and/or radiotherapy) prior to the pathological diagnosis of MTVSs. The mean size of the MTVSs was 35.1 ± 13.2mm. The mean Ki-67 index was 30.6% ± 18.8%. Twenty-four (49.0%) patients underwent gross total resection, 25 (51.0%) patients underwent incomplete resection. Twenty-five (44.6%) underwent adjuvant radiotherapy (RT) postoperatively. During the average follow-up of 9.9 ± 9.5 months (range, 0-40 months), 37 (82.2%) patients developed a local recurrence or metastasis. Forty-seven (73.4%) patients died of tumor progression or postoperative complications. The overall 1-year and 2-year survival rate was 42.3% and 18.6% respectively. Log-rank testing for Kaplan-Meier survival analysis identified that size (P = 0.047) and adjuvant radiotherapy (P=0.001) were significant prognostic factors for OS. Multivariate analysis revealed that adjuvant RT was the only prognostic factor for longer OS (P = 0.005). Conclusions MTVSs are rare, fatal disease, prone to recur and metastasize rapidly, resulting in death in most of the cases. We found that GTR did not improve the survival in MTVSs but postoperative adjuvant RT can significantly improve the OS, and we recommend early postoperative RT in MTVSs regardless of extent of resection.